Agentic AI Initiatives: Autonomous Database Operations in Databricks - Santosh Kumar Sana (International Journal of Computational and Experimental Science and Engineering, 2026)
This article presents the Databricks Agent Bricks framework for autonomous database management and demonstrates its effectiveness across PostgreSQL, MySQL, MongoDB, and SQL Server environments. The framework establishes a distributed multi-agent architecture with specialized database agents coordinating through intelligent abstraction layers and machine learning-driven decision algorithms. Reinforcement learning-based self-healing workflows enable predictive performance optimization, automated remediation, and intelligent indexing strategies based on historical patterns and real-time telemetry analysis. Integration with Apache Airflow supports dynamic backup DAG generation, cross-database consistency coordination, and intelligent scheduling that minimizes production impact during maintenance operations. Cloud-native patterns enable hybrid operation with Azure Flexible Servers while preserving comprehensive security frameworks, compliance automation, and cost optimization capabilities. Validation in representative enterprise workloads demonstrates that Agent Bricks reduces mean time to remediation by approximately forty-five percent, improves system availability by thirty-two percent, and lowers operational resource consumption by twenty-eight percent compared to traditional manual database administration approaches. Performance benchmarking across heterogeneous database environments confirms significant improvements in query response times, automated incident resolution, and proactive capacity management, providing empirical evidence for the transformative value of agentic AI implementations in enterprise database operations.